2005
DOI: 10.1128/jvi.79.17.11392-11402.2005
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the pRb-Dependent and pRb-Independent Functions of E7 In Vivo

Abstract: High-risk human papillomaviruses encode two oncogenes, E6 and E7, expressed in nearly all cervical cancers. Although E7 protein is best known for its ability to inactivate the retinoblastoma tumor suppressor protein, pRb, many other activities for E7 have been proposed in in vitro studies. Herein, we describe studies that allowed us to define unambiguously the pRb-dependent and -independent activities of E7 for the first time in vivo. In these studies, we crossed mice transgenic for human papillomavirus 16 E7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
90
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 70 publications
(95 citation statements)
references
References 62 publications
4
90
1
Order By: Relevance
“…The p53 and Rb tumor-suppressor genes are crucial in cell cycle regulation checkpoints and are common targets of inactivation by viral oncogenes, including large T antigen of SV40 virus (De Luca et al, 1997) and E6 and E7 of human papilloma virus (Balsitis et al, 2005). However, functional interactions of EBV oncogenes with tumor-suppressor genes during NPC development are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The p53 and Rb tumor-suppressor genes are crucial in cell cycle regulation checkpoints and are common targets of inactivation by viral oncogenes, including large T antigen of SV40 virus (De Luca et al, 1997) and E6 and E7 of human papilloma virus (Balsitis et al, 2005). However, functional interactions of EBV oncogenes with tumor-suppressor genes during NPC development are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In these mice, the HPV oncogenes are directed in their expression from the keratin 14 (K14) promoter, which targets expression of the viral oncogenes to the same basal compartment of stratified epithelia as observed in natural HPV infections. Furthermore, extensive analyses of these mice have shown that the HPV16 E6 and E7 oncoproteins display the same capacity to inactivate relevant cellular targets, including but not limited to p53 and pRb, respectively, as has been documented to occur in HPV-infected human epithelia (10,(21)(22)(23)(24)(25). From our studies, we have learned that these oncogenes not only possess properties that distinguish one from the other, but also that those properties may vary in a tissue-dependent manner.…”
Section: Introductionmentioning
confidence: 99%
“…In line with previous studies, we could confirm an intimate relationship between Ki-67 and p21 CIP1/WAF1/SDI1 expression (P = 0.0001; refs. 5,6,25,35,[44][45][46]. 12 On the other hand, AI and MI do not seem to be as sensitive markers of p21 CIP1/WAF1/SDI1 upregulation, albeit related to it with a lower statistical power (P = 0.05 and 0.013, respectively).…”
Section: Discussionmentioning
confidence: 88%
“…Earlier studies on cell cycle proteins and their associations with HPV infections in cervical lesions were focused on interactions between E7 and p105 (7,37,(40)(41)(42) followed by the recent interest in p107 and p130 (11)(12)(13)(14)(15)(16)43). The HPV interactions with p21 CIP1/WAF1/SDI1 have received some attention only recently (5,6,(44)(45)(46)(47)(48), and even less reports are available on cyclin A expression and its eventual prognostic value in cervical cancer (8,(49)(50)(51). Thus, it was of interest to elucidate how the differential expression of these cell cycle regulators relates to the different intermediate end point markers in cervical carcinogenesis based on immunohistochemical staining of the baseline biopsies from Pap smear -positive and/or HCII-positive women followed-up as part of the original New Independent States Cohort study (26)(27)(28)(29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation